2016
DOI: 10.1080/15513815.2016.1175529
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS4 and Oxidative/Antioxidative Status in Preterm Premature Rupture of Membranes

Abstract: ADAMTS4, TOS, and ARES levels were higher and TAS level was lower in PPROM patients than the normal healthy control group which had healthy amniotic membranes at term. As a result, ADAMTS4 may have a role in the pathogenesis by causing increased oxidative and inflammatory environment in PPROM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Researchers found TOS to be higher in the maternal blood (Clerici et al, 2012; Ilhan et al, 2015; Soydinç et al, 2012, 2013) and vaginal washing fluid (Soydinc et al, 2013) in PTB compared to TB. TOS levels were significantly higher in amniotic tissue obtained at birth for women with pPROM compared to the term control group (Ozler et al, 2016). Findings collectively suggest that a local and systemic dysregulated redox environment may be associated with PTB.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…Researchers found TOS to be higher in the maternal blood (Clerici et al, 2012; Ilhan et al, 2015; Soydinç et al, 2012, 2013) and vaginal washing fluid (Soydinc et al, 2013) in PTB compared to TB. TOS levels were significantly higher in amniotic tissue obtained at birth for women with pPROM compared to the term control group (Ozler et al, 2016). Findings collectively suggest that a local and systemic dysregulated redox environment may be associated with PTB.…”
Section: Resultsmentioning
confidence: 77%
“…Pressman et al (2011) found no differences in TAS in amniotic fluid between PTB and TB specimens. Ozler et al (2016), however, found that TAS trended lower in amniotic tissue obtained at birth for women with pPROM compared to the term control group. Together these inconclusive findings suggest that a dysregulated redox environment may be associated with PTB and is location specific.…”
mentioning
confidence: 76%
See 1 more Smart Citation